Θαλεροί τ᾽ αἰζηοί: hunting scenes in Mycenaean pictorial tradition and Homeric epic - Carbonari , Massimiliano; Voutsaki , Sofia; Klooster , Jacqueline J.H. (Journal of Greek Archaeology, 2024)
This paper addresses the visual language of a specific set of Mycenaean wall-paintings that depict hunting scenes. Specifically, it aims to investigate the purposes and modes of their depiction. It will be argued that the recurrence of hunting scenes, and specifically boar hunting scenes, in the Late Bronze Age (LBA) Greek wall painting tradition refers to a set of common values and ideals, linked to the visualisation of an elite, or palatial ideology, whose elevated status these scenes have to convey and celebrate. To better understand the mechanisms through which these aspects relate to each other, the analysis of Homeric epic, where hunting, warfare, and the expression of human excellence are deeply intertwined, will offer a stimulating field of comparison.